Manajemen Program Pembiasaan Shalat Berjamaah dalam Membentuk Karakter Disiplin Siswa - Abdurachman, Abdurachman; Hanafiah, Nanang; Sukandar, Ahmad (CV. Media Publikasi Profesional, 2021)
Discipline in this day and age is still a difficult thing to apply in life, especially the problem of time discipline, many young people do not care about time. Discipline character is a condition that is created and formed through the process of a series of behaviors that show the values ​​of obedience, obedience, loyalty, order and order. Education is a human civilizing process, and schools are formal institutions to civilize humans. The formation of school culture begins with a process of habituation that is carried out in a planned, integrated, systematic and organized manner. One of the habituation programs carried out at SMP Plus Al-Ittihad Cianjur is the habit of praying fardhu and sunnah prayers in congregation. The purpose of the research in this thesis is to describe the planning, implementation, evaluation, and the things that support and hinder the habituation program for congregational prayers. To discuss these problems, data was collected in the field by applying the instruments of interview, observation and documentation. The data obtained were then analyzed through a qualitative approach with a descriptive study method. The results of the study at SMP Plus Al-Ittihad Cianjur explained that the planning of the congregational prayer habituation program had been formulated in the form of a work program that was in line with the Vision and Mission of SMP Plus Al-Ittihad Cianjur. Plus Al-Ittihad Cianjur through habituation of congregational Fardhu and Sunnah prayers. Evaluation of the congregational prayer habituation program focused on timeliness in carrying out congregational prayers between groups of students who prayed in congregation at the beginning of time and groups of students who prayed in congregation who came late. -Ittihad Cianjur, as well as adequate facilities and infrastructure. The inhibiting factors for the congregational prayer habituation program come from students such as a sense of laziness and low student motivation. Thus, the implications of the congregational prayer habituation program have a positive impact on students, namely increasing faith and piety, praying five times a day without feeling forced. Students who carry out the habit of praying in congregation early in time have a high discipline and responsibility attitude, for example entering class on time, always doing schoolwork well and other obligations, so that they have achievements in both academic and non-academic fields. In addition, students who always carry out the habit of praying together at the beginning of time, they have good morals towards teachers (ustadz-ustadz) and friends and the people around them, in terms of speech as well as their attitudes and behavior.